Pharmaceutical care – a chance or necessity in the context of Polish self-medication - Majchrowska, Anita (Polish Journal of Public Health, 2018)
Independent Medical Sociology Unit, Faculty of Health Sciences, Medical University of Lublin, PolandIntroduction. The modern pharmaceutical care is supposed to meet numerous demands resulting from the presence and broad availability of OTC medicines. In this case the pharmacist becomes the primary advisor as for the application of medicines which are not prescribed by a doctor.Aim. The aim of the study was to recognize the position of pharmacists employed in the pharmacy towards pharmaceutical care, possibilities to conduct it and barriers of its implementation.Material and method. The researchers conducted a survey with elements of a questionnaire interview. The number of 186 pharmacists who work in pharmacies in the province of Lublin took part in the research.Results. The surveyed perceive the benefits of performing pharmaceutical care: increased prestige of the profession, greater satisfaction with their job – 44.9% choices for each; increase of the effectiveness of pharmacotherapy (54.6%) and treatment (44.3%). The major barriers to introducing pharmaceutical care include insufficient education of pharmacists (33.7%) and lack of solid co-operation with the doctor (32.6%).Conclusions. Pharmacists are aware of the importance of pharmaceutical care, although they identify a number of barriers which hinder its effective introduction.